Answer:
![S_n=(1)/(2)-(1)/(n+2)](https://img.qammunity.org/2023/formulas/mathematics/college/y6q5i5w3v50g9jko7s8n6af8pqx22420wd.png)
![S_1=(1)/(2 \cdot 3)](https://img.qammunity.org/2023/formulas/mathematics/college/9svwoujugmaqstdshmv3k2g0d25utvdq7a.png)
![S_k=(1)/(2)-(1)/(k+2)](https://img.qammunity.org/2023/formulas/mathematics/college/cs0j812sap2tdhtantocb7klaa5huyw4gl.png)
![a_(k+1)&=(1)/((k+2)(k+3))](https://img.qammunity.org/2023/formulas/mathematics/college/bxex0pj91i0mmey8ux9gjdksssgbhn4bvd.png)
![S_(k+1)=(1)/(2)-(1)/(k+3)](https://img.qammunity.org/2023/formulas/mathematics/college/xwgd9t9vre1jo4j9b8gcwkjj6ih0n89vt8.png)
Explanation:
Given sequence:
![(1)/((2\cdot3))+(1)/((3\cdot4))+(1)/((4\cdot5))+(1)/((5\cdot6))+...+(1)/((n+1)(n+2))](https://img.qammunity.org/2023/formulas/mathematics/college/1akr22elk78pfewfhy7ivoft34zw4587ib.png)
Rewrite the numerator as the subtraction of the first number of the denominator from the second number of the denominator:
![=(3-2)/((2\cdot3))+(4-3)/((3\cdot4))+(5-4)/((4\cdot5))+(6-5)/((5\cdot6))+...+((n+2)-(n+1))/((n+1)(n+2))](https://img.qammunity.org/2023/formulas/mathematics/college/o6m9chircfm4k0yzbb4bmzy0d6efh6gnor.png)
Simplify:
![=\left((3)/(6)-(2)/(6)\right)+\left((4)/(12)-(3)/(12)\right)+\left((5)/(20)-(4)/(20)\right)+\left((6)/(30)-(5)/(30)\right)+...+\left((1)/((n+1))-(1)/((n+2))\right)](https://img.qammunity.org/2023/formulas/mathematics/college/ywfsmjb1jq2s7l3ffnpbipk3hp0ihzk9xj.png)
![=\left((1)/(2)-(1)/(3)\right)+\left((1)/(3)-(1)/(4)\right)+\left((1)/(4)-(1)/(5)\right)+\left((1)/(5)-(1)/(6)\right)+...+\left((1)/((n+1))-(1)/((n+2))\right)](https://img.qammunity.org/2023/formulas/mathematics/college/aw0nxeuc04me05u3cnmbr2zjcldbex6v8j.png)
All fractions cancel except the first and last.
Therefore the formula for the sum of the given sequence is:
![\boxed{S_n=(1)/(2)-(1)/(n+2)}](https://img.qammunity.org/2023/formulas/mathematics/college/c80uojdcsdlc72x9qukmv7qtw23w6p74e5.png)
Substitute n = 1 into the formula to prove its validity:
![\begin{aligned}n=1 \implies S_1&=(1)/(2)-(1)/(1+2)\\\\&=(1)/(2)-(1)/(3)\\\\&= (3)/(2 \cdot3)-(2)/(3 \cdot2)\\\\&= (3-2)/(2 \cdot3)\\\\&=(1)/(2 \cdot3) \end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/zudmqnbuqv39kzww6qginkzzh58zudi076.png)
Hence proving the validity of the formula.
Assume the formula is valid for n = k :
![\implies S_k=(1)/((2\cdot3))+(1)/((3\cdot4))+(1)/((4\cdot5))+(1)/((5\cdot6))+...+(1)/((k+1)(k+2))](https://img.qammunity.org/2023/formulas/mathematics/college/mjx8ulb8zf27s31jbzg9jcj8huordcdtiw.png)
![\implies S_k=(1)/(2)-(1)/(k+2)](https://img.qammunity.org/2023/formulas/mathematics/college/o75rxn0jvqlr7fhrsanp1kzip491k6evzq.png)
Therefore:
![\begin{aligned}S_(k+1)&=(1)/(2)-(1)/(k+1+2)}\\\\&= (1)/(2)-(1)/(k+3)}\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/zu502n915a547oh7f2odgdstwq6oyby4ds.png)
![\textsf{Given} \; \; \; S_(k+1)=S_k+a_(k+1)\;\;\; \textsf{then}:](https://img.qammunity.org/2023/formulas/mathematics/college/cuay3xpuqh14jd3p0nkzetsx209r2h9x4y.png)
![\begin{aligned}S_(k+1)&=S_k+a_(k+1)\\\\(1)/(2)-(1)/(k+3)&=(1)/(2)-(1)/(k+2)+a_(k+1)\\\\a_(k+1)&=(1)/(2)-(1)/(k+3)-\left((1)/(2)-(1)/(k+2)\right)\\\\a_(k+1)&=-(1)/(k+3)+(1)/(k+2)\\\\a_(k+1)&=(1)/(k+2)-(1)/(k+3)\\\\a_(k+1)&=(k+3)/((k+2)(k+3))-(k+2)/((k+2)(k+3))\\\\a_(k+1)&=(k+3-(k+2))/((k+2)(k+3))\\\\a_(k+1)&=(1)/((k+2)(k+3))\end{aligned}](https://img.qammunity.org/2023/formulas/mathematics/college/rsxvakftz57buhe2ryrhvxlzlcr6oxp16n.png)
![\textsf{Use the equation for\;\;$a_(k+1)$\;\;and\;\;$S_k$\;\;to find the equation for\;\;$S_(k+1)$}:](https://img.qammunity.org/2023/formulas/mathematics/college/6sfeyjahtj5jq2b6ssqvl8ouvbswj4u7s5.png)
![\implies S_(k+1)=S_k+a_(k+1)](https://img.qammunity.org/2023/formulas/mathematics/college/70nfkh4jbdtxdh47hubjjnfaucx365iuav.png)
![\implies S_(k+1)=(1)/(2)-(1)/(k+2)}+(1)/((k+2)(k+3))](https://img.qammunity.org/2023/formulas/mathematics/college/7iq6utxw9pu2zmvufxgujc555l7eqeyyt1.png)
![\implies S_(k+1)=(1)/(2)+(1)/((k+2)(k+3))-(1)/(k+2)}](https://img.qammunity.org/2023/formulas/mathematics/college/z43zlie5j3hk7o4h76mrzhb4u3mt125h1l.png)
![\implies S_(k+1)=(1)/(2)+(1)/((k+2)(k+3))-(k+3)/((k+2)(k+3))](https://img.qammunity.org/2023/formulas/mathematics/college/2jyusr2yc4a5ymmv9vx5nqwaykxj7rnk83.png)
![\implies S_(k+1)=(1)/(2)-(k+2)/((k+2)(k+3))](https://img.qammunity.org/2023/formulas/mathematics/college/q3rwq6ymnt236191f30gzfapntkw5k77sm.png)
![\implies S_(k+1)=(1)/(2)-(1)/(k+3)](https://img.qammunity.org/2023/formulas/mathematics/college/onxdh000urd8jj6r8yhyvrq4902ssg1fuu.png)